2022
DOI: 10.3390/pharmaceutics14030470
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Stabilized Freeze-Dried Silica/Chitosan Nanoparticles for Improved Terconazole Ocular Bioavailability

Abstract: This research assesses the beneficial effects of loading terconazole, a poorly water-soluble antifungal drug in silica/chitosan nanoparticles (SCNs) for ocular delivery. Nanoparticles were fabricated by the simple mixing of tetraethyl ortho silicate (TEOS) and chitosan HCl as sources of silica and nitrogen, respectively, along with alcoholic drug solution in different concentrations. Freeze-dried nanoparticles were fabricated using cyclodextrins as cryoprotectants. SCNs were assessed for their particle size, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 80 publications
(80 reference statements)
2
7
0
Order By: Relevance
“…The modification by freeze-drying showed the highest percentage yield. These results were similar to those obtained by Zaghloul et al in their study on Silica/Chitosan for improving the solubility of Terconazole ( Zaghloul et al, 2022 ).
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…The modification by freeze-drying showed the highest percentage yield. These results were similar to those obtained by Zaghloul et al in their study on Silica/Chitosan for improving the solubility of Terconazole ( Zaghloul et al, 2022 ).
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…It was observed that upon increasing Syloid ® amount in the drug: Syloid ® weight ratio from 1:1 and 1:2 to 1:4 and 1:6, there was a significant decrease ( p < 0.05 ) in DL%. This is in logical accordance with the increase in the total solids relative to a constant drug amount (decrease mass ratio of drug to microparticles) (Zaghloul et al., 2022 ).…”
Section: Resultssupporting
confidence: 72%
“…Unfortunately, its poor aqueous solubility limits its ocular application. The literature sheds the light on several studies investigating the use of terconazole for ocular delivery applying various formulation techniques, including the fabrication of silica/chitosan nanoparticles (Zaghloul et al., 2022 ) and cationic polymeric nanoparticles (Mohsen, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…When a cryoprotectant reaches a certain temperature, it vitrifies, creating a glassy matrix that can shield nanoparticles from the ice’s mechanical stress. The majority of research on cryoprotectants show their inclusion improves liposome stability [ 149 ]. In essence, the efficacy of freeze-drying to maintain liposome stability in an aqueous state depends on a complex relationship between protectants and bilayer composition, not merely the kind and position (the inner core or bulk water) of the protectant or the determination of process parameters.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%